Book Review: Family Wars: Stories and Insights from Famous Family Business Feuds - Harris Turino; Adhi Setyo Santoso (International Journal of Family Business Practices, 2020)
Grant Gordon and Nigel Nicholson in their book with the title “Family Wars: Stories and Insights from Famous Family Business Feuds” (2010) argue that in the business world, family firms are common things. Many interesting things can be learned from them. Some people say that the family business is an inimitable advantage, but there are many conflicts in it, and some of them result in business failure. In this book, the author describes the various forms of conflict and its causes, proposing how a family should deal with conflict is and how to adapt to change. This book is the result of the author's research on conflict cases in family companies and is supported by theories taken from references.In this section, we provide the critical review as our response.